Personal brand management marketing human value - Waller, Talaya (Management for professionals., 2020)
This book is the definitive resource for understanding the phenomena and process of personal brand management as it becomes increasingly valued in a global economy. By providing a research-based, theoretical framework, the author distills the concept of personal branding as it is applicable to individuals throughout all stages of career development as well as across industries and disciplines. Extensively researched with numerous case studies, this book clearly outlines the strategic process of evaluating the economic value of a personal brand to manage and scale it accordingly. The author, an expert in the field of personal brand strategy and management, argues that a business is what a person or organization does, but the brand is what people expect from that person or organization. The two must align, and the books conceptual framework explains the theory and practice behind personal branding to accomplish this synergism. The consequence of the digital age is unprecedented visibility for individuals and businesses. As they engage with one another in more and more virtual spaces, the need for understanding and managing the evolving complexity of this 'personal engagement is an economic reality. For this reason, the framework in this title provides insight and perspective on all phases of a brand in its recursive life cycle both on and offline. By providing clarity and structure to the topic as well as practical theory for its application, this title is the ultimate primer on personal branding in theory and practice.- Resumé vydavatel